2022
DOI: 10.3390/biomedicines10092089
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and COVID-19: A Narrative Review

Abstract: Type-2 diabetes mellitus (T2DM) is a chronic metabolic disorder. The incidence and prevalence of patients with T2DM are increasing worldwide, even reaching epidemic values in most high- and middle-income countries. T2DM could be a risk factor of developing complications in other diseases. Indeed, some studies suggest a bidirectional interaction between T2DM and COVID-19. A growing body of evidence shows that COVID-19 prognosis in individuals with T2DM is worse compared with those without. Moreover, various stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 74 publications
0
14
1
1
Order By: Relevance
“…Acute organ injury caused by COVID-19 can cause long-term cardiovascular [ 1083 , 1084 ], pulmonary [ 1085 ], metabolic [ 1086 ], renal [ 1086 ] and neurological [ 1087 ] damage, potentially contributing to chronic conditions that can themselves be risk factors for severe COVID-19 in subsequent infections. COVID-19 can lead to the exacerbation of asthma [ 1088 ] and neurodegenerative disorders (both Parkinson’s and Alzheimer’s disease) [ 1088 ], and increase the risk of developing mental disorders [ 1088 , 1089 ], diabetes [ 1090 , 1091 ], CKD [ 1092 ], hypertension [ 1093 ] and CVD [ 1094 ]. COVID-19 also disturbs metabolic homeostasis, and can result in a low intake of calories and greatly reduced physical activity during hospitalization, which can exacerbate frailty and biological aging [ 586 ].…”
Section: Interactions Between Effectsmentioning
confidence: 99%
“…Acute organ injury caused by COVID-19 can cause long-term cardiovascular [ 1083 , 1084 ], pulmonary [ 1085 ], metabolic [ 1086 ], renal [ 1086 ] and neurological [ 1087 ] damage, potentially contributing to chronic conditions that can themselves be risk factors for severe COVID-19 in subsequent infections. COVID-19 can lead to the exacerbation of asthma [ 1088 ] and neurodegenerative disorders (both Parkinson’s and Alzheimer’s disease) [ 1088 ], and increase the risk of developing mental disorders [ 1088 , 1089 ], diabetes [ 1090 , 1091 ], CKD [ 1092 ], hypertension [ 1093 ] and CVD [ 1094 ]. COVID-19 also disturbs metabolic homeostasis, and can result in a low intake of calories and greatly reduced physical activity during hospitalization, which can exacerbate frailty and biological aging [ 586 ].…”
Section: Interactions Between Effectsmentioning
confidence: 99%
“…While individuals with type 2 diabetes have more coexisting comorbidities (eg, obesity and kidney impairment) that compound adverse COVID-19 outcomes, diabetes per se also causes worse COVID-19 outcomes as evidenced by the increased risk of adverse outcomes with worse glycemic control . The pathophysiologic mechanisms involve reduced viral clearance and an enhanced inflammatory state . Although COVID-19 vaccination has proven efficacy in protection against severe disease, patients with diabetes may have an impaired immune response to vaccination against COVID-19 .…”
Section: Introductionmentioning
confidence: 99%
“…More intriguingly, a recent meta-analysis has reported that newly diagnosed diabetes is commonly observed in COVID-19 patients [9][10][11]. The world has raised concerns about a bi-directional relationship between these two health conditions [12].…”
Section: Introductionmentioning
confidence: 99%